2018
DOI: 10.1017/s0029665118000058
|View full text |Cite
|
Sign up to set email alerts
|

Does dietary nitrate say NO to cardiovascular ageing? Current evidence and implications for research

Abstract: CVD are characterised by a multi-factorial pathogenesis. Key pathogenetic steps in the development of CVD are the occurrence of endothelial dysfunction and formation of atherosclerotic lesions. Reduced nitric oxide (NO) bioavailability is a primary event in the initiation of the atherosclerotic cascade. NO is a free radical with multiple physiological functions including the regulation of vascular resistance, coagulation, immunity and oxidative metabolism. The synthesis of NO proceeds via two distinct pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 124 publications
0
33
0
Order By: Relevance
“…Indeed, in the large-scale PREDIMED trial, CVD incidence was reduced by 31% and 28% with an There are several mechanisms through which the MedDiet could improve endothelial function, which may account for the beneficial effects observed in this study. Firstly, the MedDiet augments the bioavailability of nitric oxide (NO) (38), which is essential for healthy endothelial function due to its vasodilatory, anti-atherogenic and anti-proliferative actions (5). The NO 'boosting' effects of the MedDiet may be due to antioxidant effects minimising superoxide scavenging of NO (38,39), the provision of the NO precursors inorganic nitrate (green leafy vegetables) and L-arginine (nuts, grains, legumes, and fish) (39), and/ or the upregulation of endothelial NO synthase (oily fish) (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the large-scale PREDIMED trial, CVD incidence was reduced by 31% and 28% with an There are several mechanisms through which the MedDiet could improve endothelial function, which may account for the beneficial effects observed in this study. Firstly, the MedDiet augments the bioavailability of nitric oxide (NO) (38), which is essential for healthy endothelial function due to its vasodilatory, anti-atherogenic and anti-proliferative actions (5). The NO 'boosting' effects of the MedDiet may be due to antioxidant effects minimising superoxide scavenging of NO (38,39), the provision of the NO precursors inorganic nitrate (green leafy vegetables) and L-arginine (nuts, grains, legumes, and fish) (39), and/ or the upregulation of endothelial NO synthase (oily fish) (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of functional and structural integrity of the endothelium is thought to be an early pathogenic step in the development of atherosclerotic lesions and the subsequent onset of cardiovascular diseases (CVD) (3). Therefore, the endothelium has been identified as a tractable physiological target for therapeutic interventions designed to reduce risk for CVD such as stroke, coronary heart disease or peripheral arterial disease (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…A key catalyst for this change was the discovery that nitrate is a substrate for production of the multifunctional gasotransmitter nitric oxide11 12 and, so, may influence a range of nitric oxide-mediated physiological processes with potentially beneficial effects. For example, several investigations have demonstrated that dietary supplementation with inorganic nitrate, typically in doses between 4 and 12 mmol/day (~250–750 mg/day), can reduce blood pressure (BP),13–17 improve endothelial function14 17 18 and, at least in recreationally active and moderately trained individuals, enhance exercise performance 19–24. In addition, several recent observational studies have linked increased nitrate intake with reduced risk of cardiovascular disease mortality,25 atherosclerotic vascular disease26 and ischaemic cerebrovascular disease 27…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that, with correct implementation, the MedDiet could represent an effective dietary strategy to aid healthy brain ageing in non‐Mediterranean countries such as the UK. Mechanistically, these effects may be related to favourable alterations in blood glucose and lipid profiles (Rodríguez‐Rejón et al 2014; Ros et al 2014), decreased oxidative stress and inflammation (Mena et al 2009; Urquiaga et al 2010; Casas et al 2014), augmented nitric oxide (NO) bioavailability (Siervo et al 2018; Shannon et al 2018) and modulation of the gut microbiome (Filippis et al 2016; Tosti et al 2018). In NuBrain, we will extend these encouraging initial findings using data from other large UK cohorts as outlined below (see Work Package 2).…”
Section: Nutrition and Healthy Brain Ageingmentioning
confidence: 99%